P60 Effect of Indacaterol/Glycopyrronium (IND/GLY) on patient-reported outcomes in men and women with COPD: a pooled analysis from the ignite programme. (15th November 2016) - Kostikas, K; Tsiligianni, I; Fucile, S; Mezzi, K; Shen, S; Banerji, D; Fogel, R
Abstract : Introduction: Literatures, although limited, suggest differences in the manifestations of COPD in terms of symptoms and health-related quality of life between men and women. Moreover, a pooled analysis of 6 randomised trials from the IGNITE programme showed a lower baseline dyspnoea index (greater dyspnoea) and higher baseline St. George's Respiratory Questionnaire (SGRQ) total scores (worse health related quality of life) in women compared with men 1 . Here, we report the treatment impact in patient-reported outcomes (PROs) in men and women by further investigating data from the aforementioned pooled analysis. Methods: Six trials of 24 to 62 weeks duration (ENLIGHTEN, SHINE, ILLUMINATE, ARISE, SPARK and LANTERN) from the IGNITE programme were included. Effects of IND/GLY on PROs, such as transition dyspnoea index (TDI) and SGRQ total scores, symptoms scores via electronic diary and rescue medication use, were assessed, compared with salmeterol/fluticasone (SFC), glycopyrronium (GLY), tiotropium (TIO) and placebo (PBO) in both men and women with moderate to very severe COPD. Results: Data from 6108 patients were pooled and analysed (men, n = 4719; women, n = 1389). Overall, IND/GLY showed better improvement in dyspnoea and health status at Week 26 compared with other treatments. Although, there was some variability, the effect size was generally larger in women compared with men (Table). In addition, a higher percentage of women than men treated with IND/GLY achieved the minimal clinically important difference (MCID) from baseline in TDI and SGRQ total scores versus other comparators. Similarly, there was a greater reduction of rescue medication use in women than in men that received IND/GLY versus other treatments (Table). The reduction of symptom scores in the e-Diary with IND/GLY was comparable in both genders (Table). Conclusions: IND/GLY demonstrated superior improvement in dyspnoea and health status in both men and women with COPD compared with SFC, GLY, TIO and PBO. Furthermore, the efficacy of IND/GLY in terms of PROs was found to be better in women than in men and IND/GLY could be considered as a start-up treatment vs monotherapy for women with COPD. If confirmed in further studies these data may support gender differences in PROs response to bronchodilator therapy. Reference: Fucile S, et al . Am J Respir Crit Care Med 2016;193 :A6781.